2017
DOI: 10.18553/jmcp.2017.23.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ASCO Value Framework for Anticancer Drugs at an Academic Medical Center

Abstract: Funding for this research was contributed by the University of California, San Francisco, Medical Center Campus Strategic Initiative Program. The authors have no conflicts of interest to disclose. Study concept and design were contributed primarily by Wilson, along with Wang and Patel. Kim, Dacey, and Yuen collected the data, and data interpretation was performed by Wilson and Lin. The manuscript was written by Wilson, Lin, Wang, and Tran and revised by Lin, Redondi, Brodowy, and Kroon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…To date, most published assessments of value frameworks have been primarily conceptual or editorial. [15][16][17][18][19][20][21][22][23][24] Although 2 recent analyses evaluated value frameworks' validity and reliability, the generalizability of their findings to a broader array of frameworks and drugs is uncertain. It thus remains unclear whether existing oncology value assessment frameworks provide valid and reliable measurements of a drug's or regimen's value.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most published assessments of value frameworks have been primarily conceptual or editorial. [15][16][17][18][19][20][21][22][23][24] Although 2 recent analyses evaluated value frameworks' validity and reliability, the generalizability of their findings to a broader array of frameworks and drugs is uncertain. It thus remains unclear whether existing oncology value assessment frameworks provide valid and reliable measurements of a drug's or regimen's value.…”
Section: Discussionmentioning
confidence: 99%
“… Who inputs and what evidence? American Society of Clinical Oncology (ASCO) framework [ 9 , 10 ] The American Society of Clinical Oncology To provide a formal approach to define value of cancer treatments and a tool to facilitate one-on-one discussions with patients regarding the relative value of various treatment options. Multiple Specific Outcomes Trials; expert panel; patient feedback Comparative effectiveness Research [ 11 , 12 ] - Pharmaceutical industry clinical trial professionals - Health Maintenance Organizations (HMOs) - Veterans Health Administration - To determine the intervention with the best value for that specific disease.…”
Section: Resultsmentioning
confidence: 99%
“…The study observed a Kappa coefficient of 0.11 among raters, suggesting low to fair inter-rater reliability. 56 Still, this may work to the advantage of a given health system, in weighing certain factors important to that health system more than others, thus adapting the ASCO scale to their particular needs. Third, this study had a small sample size with few medications being denied formulary addition; hence, meaningful conclusions cannot be drawn.…”
Section: Discussionmentioning
confidence: 99%